Institusi perkhidmatan kemanusiaan dan pembangunan keluarga di unit perunding dan pembangunan keluarga Jabatan Agama Islam Wilayah Persekutuan Kuala Lumpur - Ismail, Zainab (Sekolah Pembangunan Sosial, 2006)
The aim of this article is to describe the role of the Unit of Consultants and Family Development (UCFD) at Jabatan Agama Islam Wilayah Persekutuan (JAWI) in family development in Wilayah Persekutuan Kuala Lumpur. This article presents evidence that although this institution had established quite along time ago, marital conflicts and divorces in the state are still on the growing. Based on this evidence we can say that the program of family development conducted by UCFD, JAWI is not so sucsessful. However this article shows that the couples attending the counseling sessions at UCFD gained a lot of assistence from dakwah given by the counselors.